Combined and targeted drugs delivery system for colorectal cancer treatment: Conatumumab decorated, reactive oxygen species sensitive irinotecan prodrug and quercetin co-loaded nanostructured lipid carriers - Youqiang Liu; Hongxin Zhang; Haijing Cui; Futong Zhang; Liyan Zhao; Yibing Liu; Qingju Meng (Taylor & Francis Group, 2022)
Purpose Colorectal cancer (CRC) is the third most frequently diagnosed cancer and this study aimed to develop a conatumumab decorated, irinotecan prodrug and quercetin co-loaded delivery system for combined and targeted colorectal cancer treatment. Methods A conatumumab (C) decorated, irinotecan prodrug (I-p) and quercetin (Q) co-encapsulated NLC (C I-p/Q NLC) was developed. In vitro and in vivo antitumor efficiency of NLC was evaluated on CRC cells and mice xenograft. Results The results showed that the HT-29 cells uptake of C I-p/Q NLC was over 70%. Reactive oxygen species (ROS) sensitive irinotecan prodrug formulation showed improved drug release ability in hypoxic conditions. C I-p/Q NLC showed significantly higher cytotoxicity than non-decorated NLC, single drug-loaded NLC and free drugs. In vivo studies in a CRC-bearing model corroborated the capability of nanoparticles for the inhibition of cancer, leading to a reduction of tumor growth without systemic toxicity. Conclusion The conatumumab decorated, ROS sensitive prodrug contained combination nano-system is a promising platform for CRC therapy.